Logistics Dimensions and Their Influence on Online Shopping Satisfaction: Evidence from Bandung, Indonesia - Koesmariadi, Fransiska Agustina; Agusinta, Lira (Indonesian Scientific Publication, 2024)
The rapid growth of e-commerce in Southeast Asia, particularly in Indonesia, has transformed logistics into a critical factor shaping customer satisfaction. Yet, the specific contribution of individual logistics dimensions in urban Indonesian contexts remains underexplored. To address this gap, this study applies the SERVQUAL and Expectation Confirmation Theory (ECT) frameworks to examine how delivery speed, order accuracy, product condition upon arrival, tracking system effectiveness, and complaint responsiveness influence customer satisfaction among e-commerce users in Bandung. A quantitative survey of 100 active users was conducted, and data were analyzed using multiple linear regression. The results show that delivery speed (β = 0.337, p < 0.001), order accuracy (β = 0.172, p = 0.002), and product condition (β = 0.175, p = 0.002) significantly enhance satisfaction, while tracking and complaint responsiveness are not statistically significant; the model explains 57% of the variance (R² = 0.57). These findings highlight that fulfillment-related dimensions are more decisive than post-purchase support in shaping consumer evaluations. This study contributes by contextualizing SERVQUAL and ECT within Southeast Asian urban e-commerce settings and provides actionable guidance: e-commerce platforms in Indonesia should prioritize delivery speed, order accuracy, and product condition as key drivers of customer satisfaction.